P379 Effect of upadacitinib on inflammatory markers and clinical outcomes in patients with Crohn's disease in the phase 3, U-EXCEL, U-EXCEED, and U-ENDURE studies. (30th January 2023) - Vermeire, S; Danese, S; Cohen, B L; Magro, F; Chen, Y; Ha, C; Dubcenco, E; Lacerda, A P; Marced, E; Oomen, J; Garrison, A; Peyrin-Biroulet, L
Abstract: Background: Improvement in clinical outcomes and normalisation of objective markers of inflammation, high-sensitivity C-reactive protein (hs-CRP) and faecal calprotectin (FCP), are considered treatment targets per STRIDE-II guidelines. 1 We evaluated the effect of the oral selective Janus kinase inhibitor upadacitinib (UPA) on changes in hs-CRP, FCP, and clinical outcomes in patients with Crohn's disease (CD). Methods: In 2 phase 3, randomized, double-blind, placebo-controlled induction studies (U-EXCEL, NCT03345849; U-EXCEED, NCT03345836), patients with moderate-to-severe CD received 12-week treatment with UPA 45 mg (UPA45) once daily (QD) or placebo (PBO). Patients with clinical response to UPA45 were rerandomised in U-ENDURE (NCT03345823) to receive 52-week maintenance treatment with UPA 30 mg QD (UPA30), UPA 15 mg QD (UPA15), or PBO. Endpoints included marker normalisation (hs-CRP ≤ 5 mg/L, FCP ≤ 250 µg/g) in patients with elevated baseline marker levels, normal marker and clinical remission by Crohn's Disease Activity Index (CDAI < 150) or very soft/liquid stool frequency (SF)/abdominal pain score (APS) (average daily SF ≤ 2.8 and average daily APS ≤ 1, neither greater than baseline), and ≥ 50% reduction from baseline in marker values with a decrease of at least 100 points in CDAI from baseline. Median changes from baseline in marker levels were also evaluated. Non-responder imputation with no special data handling for missing data due to COVID-19 was used. Results: Of 1021 enrolled patients, 645 (63.2%) had elevated hs-CRP (> 5 mg/L) and 750 (73.5%) had elevated FCP (> 250 µg/g) levels at baseline. Significantly greater proportions of patients with elevated baseline marker levels achieved normalisation with UPA compared with PBO at week 12 (Fig 1A/B) and week 52 (Fig 2A/B; nominal P < .001 for all). Decreases in marker levels from baseline with UPA were observed as early as week 2 and were significantly greater than with PBO through week 12 (Fig 1C) and week 52 (Fig 2C; nominal P < .001 for all). Patients achieved clinical endpoints and improvements in markers at significantly higher rates with UPA45 vs PBO at week 12 (Fig 1D–F) and with UPA15 and UPA30 vs PBO at week 52 (Fig 2D–F; P < .001 for all). The safety profile of UPA in CD was previously reported and no new safety concerns were identified. Conclusion: Improvements in clinical endpoints and normalisation of objective markers of inflammation were achieved as early as week 2 with UPA45 induction and sustained with UPA15 and UPA30 maintenance therapy in patients with CD. Median changes in hs-CRP and FCP with UPA support continued improvement of inflammation up to week 52. 1. Turner D., et al. Gastroenterology. 2021;160(5):1570–1583.